Incorporation of the Lasater Clinical Judgment Rubric in evaluating the performance of nursing students in experiential settings - Cassie C. Voge; Lisa Bratzke (Journal of Nursing Education and Practice, 2026)
Background: Evaluating nursing students’ performance, in particular, clinical judgment development in experiential settings is challenging. Clinical judgment is a complex concept to define and measure. However, clinical judgment is considered a core skill and is therefore crucial to evaluate. No clinical judgment development measurement tools have been developed for use in experiential (non-simulation) settings. The purpose of this project was to incorporate an evidence-based rubric into extant tools to better evaluate student clinical judgment in experiential settings. Methods: Literature was analyzed to support curriculum and evaluation tool development. The revised Lasater Clinical Judgment Rubric was incorporated into formative and summative evaluations that were administered by undergraduate nursing faculty on a cohort of first-year nursing students (upper division admission). Results: Faculty feedback suggests that the tool is feasible for use in an experiential setting. Scores revealed growth across the academic year in all areas of clinical judgment. Conclusions: The revised Lasater Clinical Judgment Rubric is feasible and provided easily accessible documentation of clinical judgment growth across the first year of nursing school. Incorporation of the rubric may help address the practice-readiness gap and contribute to positive patient outcomes.